The impact of social media advertising on brand loyalty – a case study of "Condor" company - namoun, nesrine; bouressace, widad (Journal of Excellence for Economics and Management Research, 2024)
This study aims to investigate the impact of social media advertising on brand loyalty sfor "Condor" brand, employing a descriptive and analytical methodology and formulating a model that explains the relationship between study variables. The study utilized random sampling to distribute questionnaires to a sample of 196 customers of the "Condor" brand. Subsequently, data analysis and hypothesis testing were conducted using multiple linear regression and the Statistical Package for the Social Sciences (SPSS). The study concluded a statistically significant impact of advertising on social media on brand loyalty for "Condor". However, there were no differences found in the responses of study participants regarding study dimensions attributed to their personal variables namely gender, age, and educational level. Finally the study recommended that the company should develop and design advertisements on social media based on scientific principles and modern techniques to reach and attract consumers. Additionally, it suggested implementing comprehensive advertising campaigns that not only cover social media platforms but also include search advertising and other social networks to enhance the organization’s digital presence.